CULTURE / METACULTURE - FRANCIS MULHERN (NEW YORK ROUTLEDGE, 2000)
A stimulating, interdisciplinary survey of the conceptual and political issues involved in the notion of twentieth-century culture. This accessible study introduces important theorists including Freud, Woolf, Orwell, and Sartre.
Keywords: CULTURE